Long-Term Acclimation to Iron Limitation Reveals New Insights in Metabolism Regulation of Synechococcus sp. PCC7002 - Blanco-Ameijeiras, Sonia; Cosio, Claudia; Hassler, Christel S. (Frontiers in Marine Science, 2017)
In large areas of the ocean phytoplankton growth is limited by the scarcity of iron (Fe), an essential co-factor for multiple enzymes. Phytoplankton has hence developed strategies to survive under Fe limitation. Here, we characterize the response to Fe limitation of the cyanobacterium Synechococcus sp. PCC7002 acclimated to different Fe concentrations in chemically characterized synthetic seawater. The inorganic Fe concentrations used represent levels of Fe limitation relevant for different domains of the contemporary ocean. Combining physiological and transcriptomic approaches, we provide evidence of the progression of the physiological responses to increasing levels of Fe limitation. Our results showed a rising number of significantly regulated genes and the complexity of the response to increasing Fe limitation. Mild Fe limitation induced up-regulation of genes involved in Fe uptake, while genes involved in photosynthesis and respiration were down-regulated. Strong Fe limitation induced up-regulation of genes involved in energy metabolism and concomitant down-regulation of macronutrients uptake. Severe Fe limitation affected fine metabolic regulation of co-factors expression and activation of anti-oxidative stress responses. Our results suggest that homeostasis under long-term Fe limitation put at play dramatically different mechanisms for oxidative stress mitigation and carbon metabolism than those previously reported under Fe stress. Hence, evidence the importance of acclimation processes on the performance of cyanobacteria under Fe limitation conditions.